Bauru à moda caxiense: um estudo de caso na gastronomia da região de colonização italiana - Andrade, Vanessa Pacheco (My University, 2021)
Caxias do Sul - RS has always been known as the city of Italians. The cultural habits that characterize it are proof of the influence of Italian culture in its constitution. With the city's economic development, new cultures were introduced, which affected many of its cultural practices, including gastronomic diversification. In this context, the present study aims to analyze the importance of the "caxiense-style bauru" in the gastronomic culture of Caxias do Sul, based on the history of the Danúbio Restaurant. The methodology is qualitative in nature and oral history was the method chosen to support the research. The interviews carried out form the corpus of this study and from the analysis of the narratives emerged the categories that bring the voice to the interviewed subjects. These categories show how eating habits had value in the city's culture and how was introduced the caxiense-style bauru, becoming a typical, valued and recognized dish. The study contemplates the trajectory of the restaurant, the strength of this dish in local eating habits and contributes to the understanding of cultural habits in the region of Italian colonization. [resumo fornecido pelo autor]
Caxias do Sul - RS sempre foi conhecida como cidade de italianos. Os hábitos culturais que a caracterizam são prova da influência da cultura italiana na sua constituição. Com o desenvolvimento econômico da cidade, houve a introdução de novas culturas, o que afetou muitas de suas práticas culturais, inclusive no que diz respeito à diversificação gastronômica. Nesse contexto, o presente estudo tem como objetivo analisar a importância do "bauru à moda caxiense" na cultura gastronômica de Caxias do Sul, a partir da história do Restaurante Danúbio. A metodologia é de natureza qualitativa e a história oral foi o método escolhido para sustentar a pesquisa. As entrevistas realizadas formam o corpus deste estudo e da análise das narrativas emergiram as categorias que trazem a voz dos sujeitos entrevistados. Essas categorias evidenciam como os hábitos alimentares tinham valor na cultura da cidade e de como foi introduzido o bauru à moda caxiense, tornando-se um prato típico, valorizado e reconhecido. O estudo contempla a trajetória do restaurante, a força desse prato nos hábitos alimentares locais e contribui para a compreensão de hábitos culturais da região de colonização italiana. [resumo fornecido pelo autor]
Keywords: Turismo e gastronomia; Gastronomia - Caxias do Sul (RS); Turismo - Caxias do Sul (RS); Tourism and gastronomy; Gastronomy - Caxias do Sul (Brazil); Tourism - Caxias do Sul (Brazil)